Development Of A Quadruped Crawling Robot Prototype - Salim, Mohd Azli; Noordin, Aminurrashid; Mohamad Sapiee, Mohd Razali; Che Hasan, Mohd Hanif; Sabikan, Sulaiman; Othman, Mohd Hafifi (2012)
Although wheeled robots are commonly used, it has limited ability to move to any terrains at ease. They suffer from difficulties when travelling over uneven and rough terrains. Legged robots have an advantage over the wheeled robots in that they are suited for such situations. The implementation of legged robots normally requires many motors to move every joint in a robot leg. Additional motor will increase the construction cost, robot weight, and the demand for power supply. Moreover, robot simulation becomes more complex. This research is related to the design and development of a cost effective quadruped autonomous robot. The robot can moves according to a unique pattern using three servo motors as its actuator in each of its leg. The design of the robot is firstly made with CAD program and then the structure of the body and the leg is analyzed in order to find a correct balance and to make sure the servo motors are capable to move the robot. A prototype of the quadruped robot is fabricated and tested thoroughly. Experimental studies are carried out to test its stability issues when the robot moves. The robot is capable of moving forward, backward, turn left and turn right by crawling its way. A microcontroller is used as the brain of the robot assisted by two analog distance sensor for better obstacle sensing. It uses a rechargeable battery as the power supply for the microcontroller. The servo motors on the other hand are powered by another rechargeable battery. At the end of this research, a working prototype has been developed.